Capital structure determinants between domestic-owned firms and foreign-owned firms across manufacturing listed firms in Indonesia [electronic resource] - Andhika Mandala Utama, 1989-; Suresh Ramakrishnan; Melati Ahmad Anuar; Fakulti Pengurusan (2015)
Thesis (Sarjana Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2015